An Analysis of Women’s Right Manifestation of Jo March in the Little Women by Gerwig 2019 - Amelia Daulay; Pratiwi Amelia; Redika Cindra Reranta (UM Purwokerto Press, 2024)
In the 18th century, many women were unable to express their independence in their careers, marriages, and lifestyles. This contradicts Jo March's, she is support the gender equality that women and men have equal rights in all aspects. In line with this, this study aims to analyze the movements played by Jo March as the main character in the film Little Women in terms of liberal feminism. This study uses a qualitative approach method through content analysis techniques. Data collection in this study is observation which consists of watching, classifying, and cross-checking the movie. The data analysis technique used in this study is content analysis which consists of coding, classifying, discussing, and reporting. Furthermore, the result of this study are eight of the twelve types of women’s’ rights. It consists of stating personal requirements, expressing personal feelings, expressing personal opinions, prioritizing personal priority, saying 'yes' or 'no' for myself, making mistakes, changing self-mind, and saying I don’t understand.